Low-temperature nuclear heating reactors: Characteristics and application of licensing law in China - Liu, Bingyu; Liu, Jiu; Shen, Le (Frontiers in Energy Research, 2023)
As one type of small modular nuclear reactor (SMR), the development of low-temperature nuclear heating reactors (LTNHRs), which have the characteristics of small size, a large power ratio, and good adaptability, can help provide energy in winter as well as reduce greenhouse gas emissions. Despite a growing number of LTNHRs worldwide, a mature legal regulatory system specifically targeting LTNHRs remains undeveloped. Further, few discussions have focused on the prospect of regulating LTHHRs and how national and international frameworks can respond to the new and increasing development of LTNHRs. Given the growing prominence of LTNHRs, this article aims to fill in the research gap by exploring possible regulatory pathways for LTNHRs and whether the existing nuclear regulatory frameworks developed for large reactors could be sufficiently applied to LTNHRs. The article examines and analyzes the prospects and potential challenges for regulating LTHHRs, specifically in the field of licensing. In particular, the article takes the Chinese nuclear legal system as an example to analyze whether the existing legislation and regulations can meet the new requirements for licensing of LTNHRs—given their unique characteristics—in China. Finally, this article proposes suggestions to address the obstacles to regulating LTNHRs, including amending the existing international regulatory framework, improving licensing supervision throughout environmental assessment and public participation, and strengthening international legal cooperation, to ensure the robust and reasonable development of LTNHRs worldwide.